Motion correction for three‐dimensional chemical exchange saturation transfer imaging without direct water saturation artifacts. (13th March 2022) - Breitling, Johannes; Korzowski, Andreas; Kempa, Neele; Boyd, Philip S.; Paech, Daniel; Schlemmer, Heinz‐Peter; Ladd, Mark E.; Bachert, Peter; Goerke, Steffen
Abstract : In chemical exchange saturation transfer (CEST) MRI, motion correction is compromised by the drastically changing image contrast at different frequency offsets, particularly at the direct water saturation. In this study, a simple extension for conventional image registration algorithms is proposed, enabling robust and accurate motion correction of CEST‐MRI data. The proposed method uses weighted averaging of motion parameters from a conventional rigid image registration to identify and mitigate erroneously misaligned images. Functionality of the proposed method was verified by ground truth datasets generated from 10 three‐dimensional in vivo measurements at 3 T with simulated realistic random rigid motion patterns and noise. Performance was assessed using two different criteria: the maximum image misalignment as a measure for the robustness against direct water saturation artifacts, and the spectral error as a measure of the overall accuracy. For both criteria, the proposed method achieved the best scores compared with two motion‐correction algorithms specifically developed to handle the varying contrasts in CEST‐MRI. Compared with a straightforward linear interpolation of the motion parameters at frequency offsets close to the direct water saturation, the proposed method offers better performance in the absence of artifacts. The proposed method for motion correction in CEST‐MRI allows identification and mitigation of direct water saturation artifacts that occur with conventional image registration algorithms. The resulting improved robustness and accuracy enable reliable motion correction, which is particularly crucial for an automated and carefree evaluation of spectral CEST‐MRI data, e.g., for large patient cohorts or in clinical routines. Abstract : In this study, a simple extension for conventional image registration algorithms is proposed, enabling robust and accurate motion correction of CEST‐MRI data without direct water saturation artifacts. The performance of different approaches was investigated using ground truth datasets, generated from 10 3D in vivo measurements at 3 T, corrupted with realistic random rigid motion patterns and noise. In comparison with other approaches, the proposed method achieved more accurate and robust results.